2021
DOI: 10.3389/fspas.2021.777554
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dimensional Bianchi Type-I Cosmological Models With Massive String in General Relativity

Abstract: Here we studied Bianchi type-I cosmological models with massive strings in general relativity in five dimensional space time. Out of the two different cases obtained here, one case leads to a five dimensional Bianchi type-I string cosmological model in general relativity while the other yields the vacuum Universe in general relativity in five dimensional space time. The physical and geometrical properties of the model Universe are studied and compared with the present day’s observational findings. It is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Some authors have demonstrated in their research that the four-dimensional spacetimes expand while the fifth dimension contracts or remains constant. Recently [13][14][15], several authors have studied higher dimensions using different cosmological Models.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have demonstrated in their research that the four-dimensional spacetimes expand while the fifth dimension contracts or remains constant. Recently [13][14][15], several authors have studied higher dimensions using different cosmological Models.…”
Section: Introductionmentioning
confidence: 99%